1953
DOI: 10.2105/ajph.43.8.1011
|View full text |Cite
|
Sign up to set email alerts
|

Newburgh-Kingston Caries Fluorine Study. V. Pediatric Aspects—Continuation Report

Abstract: Here is just the factual sort of material that all in public health need to reassure timid or doubtful people who may be influenced by the baseless charges about the dangers of fluoridation shouted at public nmeetings, or set forth in letters to the editor. Each point made in this progress report should be indelibly planted in the minds of those of us who meet the public.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1953
1953
2005
2005

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…This led to the hypothesis that fluoridated water prevents the dental caries. In 1945, the Newburgh-Kingston caries-fluorine study, a prospective study, confirmed that the more fluorine in the water given to a study population, the fewer dental caries (Schlesinger, Overton et al 1950;Dean 1953;Schlesinger, Overton et al 1953;Ast, Smith et al 1956;Dean 1956;Schlesinger, Overton et al 1956). This study led to new public health policies recommending that fluorine be added in drinking water or that toothpastes and fluorine tables or solution be used in the prevention of cavities.…”
Section: Ii1 Fluoridated Water and Tooth Decaymentioning
confidence: 99%
“…This led to the hypothesis that fluoridated water prevents the dental caries. In 1945, the Newburgh-Kingston caries-fluorine study, a prospective study, confirmed that the more fluorine in the water given to a study population, the fewer dental caries (Schlesinger, Overton et al 1950;Dean 1953;Schlesinger, Overton et al 1953;Ast, Smith et al 1956;Dean 1956;Schlesinger, Overton et al 1956). This study led to new public health policies recommending that fluorine be added in drinking water or that toothpastes and fluorine tables or solution be used in the prevention of cavities.…”
Section: Ii1 Fluoridated Water and Tooth Decaymentioning
confidence: 99%